2003
DOI: 10.1002/j.1939-4640.2003.tb02687.x
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Mitochondrial Mutations as a Cause of Low Sperm Motility

Abstract: We report the unique case of a 28-year-old man who, in spite of having a varicocele and a sperm concentration of 5 million/mL, of which 10% were motile and 20% had normal forms (oligoasthenoteratozoospermia [OAT]), was fertile. This was confirmed by paternity testing using 16 autosomal and 6 Y-chromosomal short tandem repeat (STR) loci. An analysis of mitochondrial genes that included cytochrome oxidase I (COI), cytochrome oxidase II (COII), adenosine triphosphate synthase6 (ATPase6), ATPase8, transfer ribonuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 25 publications
0
55
0
1
Order By: Relevance
“…Montiel-Sosa et al (2006) reported associations between distinct sub-haplogroups within the U haplogroup and variation in sperm motility and attempted to map these patterns to particular polymorphisms that distinguish the sub-haplogroups. Various other studies linked particular point mutations or deletions in human mtDNA to sperm dysfunction (Folgerø et al 1993, Huang et al 1994, Kao et al 1995, Fadic et al 1997, Lestienne et al 1997, Kao et al 1998, Holyoake et al 2001, St John et al 2001, Spiropoulos et al 2002, Thangaraj et al 2003, Kumar et al 2009, Baklouti-Gargouri et al 2013a,b, Colagar et al 2013, Chari et al 2015, Lu et al 2015). Yet, some caution must be applied to interpreting correlations of the type presented in these studies, since the patterns could be mediated by other confounding factors, such as differences in nuclear genetic structure between groups of individuals possessing the different mtDNA haplotypes.…”
Section: Human Case Studiesmentioning
confidence: 99%
“…Montiel-Sosa et al (2006) reported associations between distinct sub-haplogroups within the U haplogroup and variation in sperm motility and attempted to map these patterns to particular polymorphisms that distinguish the sub-haplogroups. Various other studies linked particular point mutations or deletions in human mtDNA to sperm dysfunction (Folgerø et al 1993, Huang et al 1994, Kao et al 1995, Fadic et al 1997, Lestienne et al 1997, Kao et al 1998, Holyoake et al 2001, St John et al 2001, Spiropoulos et al 2002, Thangaraj et al 2003, Kumar et al 2009, Baklouti-Gargouri et al 2013a,b, Colagar et al 2013, Chari et al 2015, Lu et al 2015). Yet, some caution must be applied to interpreting correlations of the type presented in these studies, since the patterns could be mediated by other confounding factors, such as differences in nuclear genetic structure between groups of individuals possessing the different mtDNA haplotypes.…”
Section: Human Case Studiesmentioning
confidence: 99%
“…In another study, the T9098C transition was detected only in infertile cases, and the finding of this mutation was statistically significant when compared to controls [138,140]. Thangaraj et al, [141] also established that mitochondrial mutations in sperms can cause low sperm motility that is not related to infertility. They observed 10 SNPs in the ATPase6 gene in the sperm DNA of an oligoasthenoteratozoospermic man.…”
Section: The Usp26 Gene Mutationsmentioning
confidence: 99%
“…While the laboratory classification of oligozoospermia and normozoospermia is based on the sperm counts with a cutoff of 15 million/ml [42], the correlation of these counts to fertility is often poor and an individual can father a child even at sperm concentrations lower then this cutoff [13,40]. Thus, the fertility status is often a misleading parameter for association based studies and it is recommended to compare the data with sperm counts.…”
Section: Discussionmentioning
confidence: 99%
“…PCR was performed at an optimized annealing temperature and has been detailed elsewhere [1,5,40]. The amplicons were further subjected to direct sequencing [5,40] using BigDye Terminator cycle sequencing kit (Applied Biosystems, Foster City USA) and 3730 DNA analyzer (Applied Biosystems). The PROGINS amplified products were loaded in a 2 % agarose gel stained with ethidium bromide and observed under UV transillumination ( Fig.…”
Section: Methodsmentioning
confidence: 99%